Rational design of surface engineered albumin nanoparticles of asiatic acid for EGFR targeted delivery to lung cancer: Formulation development and pharmacokinetics - Shukla V.N.; Vikas; Mehata A.K.; Setia A.; Kumari P.; Mahto S.K.; Muthu M.S.; Mishra S.K. (My University, 2025)
Targeted delivery of natural bioactive molecules has the potential to reduce toxicity while increasing anticancer therapeutic efficacy. Nanoparticles (NPs) conjugated with targeting ligands are widely explored because they offer better drug release profiles, biocompatibility, and tunability in particle size. The goal of this research was to create targeted nanoparticles comprised of bovine serum albumin (ALB) and asiatic acid (ASA) conjugated with cetuximab antibodies, which bind specifically to cells overexpressing the EGFR (epidermal growth factor receptor). Physicochemical characterization of the formulations revealed stable particles with the typical size range of approximately 200 nm. In vitro drug release tests show that the drug is released slowly over time. An in vitro MTT assay was performed on A549 and HEK-293 cells to determine the cytotoxicity of formulations. Furthermore, cellular uptake studies were conducted. Moreover, apoptosis studies and cell cycle analyses were performed on A549 cells. A concentration equivalent to the IC50 value of CTX-ASA-ALB-NPs resulted in greater apoptosis in A-549 cells compared to ASA and also led to G0/G1 phase cell cycle arrest. However, the extent of cytotoxicity of CTX-ASA-ALB-NPs in HEK-293 cells (control cells) was lower, which demonstrates the specific targeting efficiency in cancerous cells. Subsequently, in vivo investigations were conducted on Wistar rats to evaluate pharmacokinetic properties and acute toxicity. These findings suggest that ASA-ALB-NPs conjugated with an anti-EGF receptor ligand (Cetuximab) hold promise as a viable nanomedicine for specific lung cancer therapy. © 2023 Elsevier B.V.